The Treatment of Peri-Implant Diseases: A New Approach Using HYBENX® as a Decontaminant for Implant Surface and Oral Tissues - Michele Antonio Lopez; Pier Carmine Passarelli; Emmanuele Godino; Nicolò Lombardo; Francesca Romana Altamura; Alessandro Speranza; Andrea Lopez; Piero Papi; Giorgio Pompa; Antonio D'Addona (MDPI AG, 2021)
Background: Peri-implantitis is a pathological condition characterized by an inflammatory process involving soft and hard tissues surrounding dental implants. The management of peri-implant disease has several protocols, among which is the chemical method HYBENX®. The aim of this study is to demonstrate the efficacy of HYBENX® in the treatment of peri-implantitis and to compare HYBENX® with other chemical agents used in the surgical treatment of peri-implantitis. Methods: The present study included a population of ten subjects with severe peri-implantitis. The procedure used in the study involves the application of HYBENX® after open-flap debridement. Each patient has been followed for 12 months after a single application of the decontaminant agent. Clinical and radiographical parameters were recorded at baseline, 3 months, and 12 months after treatment completion. Results: At baseline, a mean pocket probing depth (PPD) of 7.3 ± 0.5 mm and a mean clinical attachment level (CAL) of 8.8 ± 0.8 mm was recorded. An average residual PPD of 4.2 ± 0.5 mm and a mean CAL of 5.2 ± 0.8 mm were observed after 1 year. Additionally, the average of bone gain was about 3.4 mm, with a mean marginal bone level (MBL) change from 5.8 mm (baseline) to 2.4 mm (12 months). In total, 90% of the treated implants reached the success rate after the 1-year follow-up. Only in one case out of ten treated implants was resolution of the disease not achieved. Conclusion: Clinical improvements highlight that the procedure of open-flap debridement (OFD) + HYBENX® may be considered an effective technique in the treatment of peri-implantitis. From the results obtained, it can be concluded that the use of HYBENX® in the surgical treatment of peri-implantitis is promising. Overall, this protocol demands further studies to better understand the role and potential benefits of HYBENX® in the treatment of peri-implantitis.